The Use of a Monopoly-Style Board Game Combined with Flashcards on the Topic of Body Systems in a Basic Science Course for 8th-Grade Students at Triamudomsuksapattanakarn Nonthaburi School - ช่างปับ, ทศพล (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The research on "The Effects of Using Monopoly-Style Board Game Combined with Flashcards on the Topic of Body Systems in Basic Science for Grade 8 Students at Triam Udom Suksa Pattanakarn Nonthaburi School" aimed to study the learning achievement and satisfaction of students towards learning using a Monopoly-style board game combined with flashcards. The sample group consisted of 80 Grade 8 students studying basic science, specifically the topic of body systems. The research employed a One Group Pretest-Posttest Design. The research tools included lesson plans, the Monopoly-style board game combined with flashcards, pre- and post-tests, and a satisfaction questionnaire. The results showed that the average post-test score after using the board game was 11.97 out of 20, representing 59.85% of the total score, with 63 students (78.75% of the total sample) passing the 50% threshold. Additionally, students expressed a high level of satisfaction (average score of 4.23 out of 5.00) with the learning experience using the board game. The highest satisfaction was reported in the areas of promoting self-directed learning and student-centered learning. The research concludes that the use of the Monopoly-style board game combined with flashcards effectively enhances learning achievement and student satisfaction in the classroom.